Article Review: Safety and Toxicity Testing of Herbal Medicines in the Development of Jamu, Standardized Herbal Medicines, and Phytopharmaceuticals - Suryani , Monica; Safitri , Alfi; Marbun , Eva Diansari; Suryani , Ade Irma; Zura , Cut Alvida (Journal of Pharmaceutical and Sciences, 2026)
Background: Safety and toxicity testing are essential stages in the development of herbal medicines to ensure therapeutic efficacy without causing adverse effects. In Indonesia, herbal products are classified into traditional herbal medicines (jamu), Standardized Herbal Medicines, and phytopharmaceuticals, each requiring different levels of scientific evidence for safety and efficacy. Objective: This study aims to review the results of safety and toxicity testing of herbal medicines in the development of jamu, Standardized Herbal Medicines, and phytopharmaceuticals in Indonesia over the last five years (2020–2025). Methods: This study employed a descriptive, qualitative literature review. Scientific articles were systematically retrieved from the Garuda, Neliti, Sinta, and Google Scholar databases using relevant keywords related to herbal medicine safety and toxicity testing. A total of twelve peer-reviewed research articles published between 2020 and 2025 met the inclusion criteria. The reviewed studies involved in vivo, in vitro, and in silico testing methods, with toxicity parameters including LD₅₀, LC₅₀, biochemical markers, and histopathological changes. Results: The findings indicate that in vivo testing is the most frequently applied method and generally demonstrates a high safety profile for most herbal preparations. Jamu products are considered safe based on empirical use and standardized raw materials. Standardized Herbal Medicines demonstrate safety through acute and subchronic toxicity evaluations. At the same time, phytopharmaceuticals exhibit the highest level of safety through comprehensive testing using combined in vivo, in vitro, and in silico approaches. Most herbal ingredients fall into the non-toxic to mildly toxic category at high doses. Conclusion: Overall, the reviewed evidence suggests that Indonesian herbal medicines, including jamu, Standardized Herbal Medicines, and phytopharmaceuticals, are generally safe when used appropriately. Strengthening multidisciplinary toxicological approaches and implementing pharmacovigilance principles are essential to ensure long-term safety and support the development of evidence-based national herbal medicines.